Past, present, and future of global health financing: a review of development assistance, government, out-of-pocket, and other private spending on health for 195 countries, 1995-2050 - Chang, Angela Y.; Cowling, Krycia; Micah, Angela E.; Chapin, Abigail; Chen, Catherine S.; Ikilezi, Gloria; Sadat, Nafis; Tsakalos, Golsum; Wu, Junjie; Younker, Theodore; Zhao, Yingxi; Zlavog, Bianca S.; et al. (The lancet, 2019)
Background - Comprehensive and comparable estimates of health spending in each country are a key input for health policy and planning, and are necessary to support the achievement of national and international health goals. Previous studies have tracked past and projected future health spending until 2040 and shown that, with economic development, countries tend to spend more on health per capita, with a decreasing share of spending from development assistance and out-of-pocket sources. We aimed to characterise the past, present, and predicted future of global health spending, with an emphasis on equity in spending across countries. - Methods - We estimated domestic health spending for 195 countries and territories from 1995 to 2016, split into three categories—government, out-of-pocket, and prepaid private health spending—and estimated development assistance for health (DAH) from 1990 to 2018. We estimated future scenarios of health spending using an ensemble of linear mixed-effects models with time series specifications to project domestic health spending from 2017 through 2050 and DAH from 2019 through 2050. Data were extracted from a broad set of sources tracking health spending and revenue, and were standardised and converted to inflation-adjusted 2018 US dollars. Incomplete or low-quality data were modelled and uncertainty was estimated, leading to a complete data series of total, government, prepaid private, and out-of-pocket health spending, and DAH. Estimates are reported in 2018 US dollars, 2018 purchasing-power parity-adjusted dollars, and as a percentage of gross domestic product. We used demographic decomposition methods to assess a set of factors associated with changes in government health spending between 1995 and 2016 and to examine evidence to support the theory of the health financing transition. We projected two alternative future scenarios based on higher government health spending to assess the potential ability of governments to generate more resources for health. - Findings - Between 1995 and 2016, health spending grew at a rate of 4·00% (95% uncertainty interval 3·89-4·12) annually, although it grew slower in per capita terms (2·72% [2·61-2·84]) and increased by less than
Global Burden of Disease Health Financing Collaborator Network: Angela Y Chang, Krycia Cowling, Angela E Micah, Abigail Chapin, Catherine S Chen, Gloria Ikilezi, Nafis Sadat, Golsum Tsakalos, Junjie Wu, Theodore Younker, Yingxi Zhao, Bianca S. Zlavog, Cristiana Abbafati, Till Winfried Bärnighausen, Jan-Walter De Neve, Jost B. Jonas, Stefan Kohler, Shafiu Mohammed [und viele weitere]
Gesehen am 29.04.2021